Strengthening Know Your Customer (KYC) and Anti-Money Laundering (AML) Policies in the Fintech Industry to Prevent Money Laundering Crimes - Rusman Rusman; Azis Budianto (Journal of World Science, 2025)
Financial Technology (Fintech) has experienced rapid development and brought innovation to the digital financial system. However, behind the convenience and efficiency offered, fintech also faces serious challenges related to Money Laundering (TPPU). This crime exploits loopholes in regulations and the ease of digital transactions to disguise illegal fund flows. Therefore, it is necessary to strengthen the prevention and law enforcement system against TPPU in the fintech ecosystem. The study aims to analyze the role of fintech in preventing TPPU and review the effectiveness of regulations that have been implemented by the government and financial institutions in Indonesia. The research method used is normative legal research with a statutory approach. The data used consists of primary data, in the form of laws and regulations related to fintech and TPPU, as well as secondary data obtained from scientific journals, books, and official reports of financial institutions such as the Financial Services Authority (OJK), Bank Indonesia (BI), and the Financial Transaction Reports and Analysis Center (PPATK). The analysis was conducted qualitatively to examine the effectiveness of the policies that have been implemented and to identify challenges in implementing TPPU prevention in the fintech sector. The results of this study are expected to contribute to the development of more effective policy strategies in dealing with money laundering in the fintech industry, as well as provide recommendations for regulators and industry players in improving compliance with the Know Your Customer (KYC) and Anti-Money Laundering (AML) principles.